'When 'tis Night, Death is Green': Vegetal Time in Nineteenth-Century Econoir. Issue 1 (2nd January 2018) - Bishop, Katherine E.
ABSTRACT: The inscrutability of plant life has made it an intriguing player in detective fiction, particularly in that which rubs against the speculative. Botanicals began figuring as de facto killers in crime fiction of the long nineteenth century, herein called econoir. While classic detective fiction undergirds traditional sociocultural power, reinforcing normativity, econoir texts decenter this nexus, in particular by confronting human time with vegetal time. In doing so, such texts destabilise the very equilibrium crime fiction narratives typically fight so hard to achieve, juxtaposing the rational world of the text with alternative, ecological logic. This reconfiguration suggests alternative ways of narrativising, knowing, and being in the world.